Derived Nouns in Austen’s Novel Sense and Sensibility - Diah Sri Lestari, Ni Putu (Udayana Journal of Social Sciences and Humanities; Vol 4 No 1 (2020): UJoSSH, February 2020DO - 10.24843/UJoSSH.2020.v04.i01.p07, 2020)
This study is entitled Derived Nouns in Austen’s Novel Sense and Sensibility . This study aims to identify kinds of derivational suffixes nouns found in Derived Nouns in Austen’s novel Sense and Sensibility and to explain meanings of the derived nouns. The data were taken from Austen’s novel Sense and Sensibility published in 1811. This study used library research and applied documentation method to collect the data. The method used in data analysis was the qualitative method. The technique of presenting data used the descriptive method for identifying the process of the derivational forming noun. This study applied the kinds of derived suffixes nouns proposed by McCarthy (2002) as the main theory, and meaning of derived nouns proposed by Haspelmath and Sims (2010) as the supporting theory. The findings showed that there were three classes; they are: suffixes forming nouns from nouns such as the suffixes –er, -ship and –hood, suffixes forming adjectives from nouns are the suffixes –ity, -ness, and –ism, and suffixes forming verb from nouns are the suffixes –ance, -ence, -ment, -ing, –((a)t)ion, and -al. The derivational meanings denoted deverbal nouns found in the data such as agent nouns and action nouns. The derivational meanings denoted deadjective nouns were quality nouns. On the other side, the derivational meanings denoted by denominal nouns were status nouns.